Mobilisasi Dini Dengan Proses Penyembuhan Luka Pada Pasien Post Op Sectio Caesarea - Ananda, Yuanita; Gusdiansyah, Edo (REAL in Nursing Journal, 2023)
Background: Sectio caesarea deliveries may be one cause of infection if treatment is done improperly. Based on the data record Medical Record TheHospital of Tk. III Dr. Reksodiwiryo of Padang action caesarea section of month Juli-Desember 2022reach 119 people the length of stay of more than three days as many as 52 people (43,69%), Post section caesarae mothers mobilize for the wound healing process. The objective of this research is to know The Related Early Mobiliasasi With Wound Healing Process in Patients Post Op Sectio Caesarea In TheHospital of Tk. III Dr. Reksodiwiryo of Padang. Methods: Type of the research is analytical with cross-sectional design. The study was conducted at The Hospital of Tk. III dr. Reksodiwiryo Padang.  When the study in Juli-Desember 2022.  The population in this study is the all patient of post op sectio caesarea di Midwifery room 119 peoples. The sample was taken with simple Random Sampling as many as 54 people. Analysa of data used univariate and bivariate by chi Square with quetionare. Results: The results showed that most of the half (50%) patients experienced healing of wounds do heal. More than half (77,8%) patients doing early mobilization. There is a significant relationship between early mobilization with wound healing at The Hospital of Tk. III dr. Reksodiwiryo Padang. Conclusion: It can be concluded that there is a relationship between early mobilization with the healing of wounds in hospital inpatient room. Tk. III Dr. Reksodiwiryo Padang. The results of this study are expected to contribute advice and information for the hospital director for consideration and determining policy related to wound healing post- op sectio caesarea.Keywords: Wound Healing, Early Mobilization